Nutcracker Syndrome ultrasonography imaging features - Yeda da Silva; Marianna Rafaelly Sforza Auerswald; Naiany Olivotto Martins; Alexia Victória Klassen; Isabelle Tomelin Rothenburg; Plauto Christopher Aranha Watanabe; Luciana Munhoz (Anais da Faculdade de Medicina de Olinda)
The Nutcracker Syndrome (NCS), also known as left renal vein (LRV) entrapment syndrome, is caused by LRV stenosis due to the angle narrowing between the superior mesenteric artery (SMA) and the aorta. The stenosis leads to dilatation of the LRV distal portion. Patients may be asymptomatic or experience hematuria, proteinuria, flank pain, pelvic congestion in women, and varicocele in men. Doppler ultrasonography (US) is an excellent diagnostic tool for NCS as it facilitates assessing LRV anatomy and physiology. This case report aimed to describe the imaging features of NCS in Doppler US and to discuss the diverse features of NCS in various imaging studies.